Implementasi Dashboard Instrumen Akreditasi 9 Kriteria BAN PT Berbasis Web pada Program Studi Sistem Informasi Fakultas Sains & Teknologi UIN Alauddin Makassar - Farida Yusuf; Didit Hermawan; Ahmad Ilham (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
Making dashboards has many functions from various aspects, one aspect that utilizes the use of the dashboard is in terms of education. In terms of education, the dashboard can be used as a forum for meeting the needs of higher education accreditation. UIN Alauddin Makassar, especially in the Information Systems Study Program, Faculty of Science and Technology, is a study program which in its accreditation implementation involves BAN-PT as an assessor of study program achievements. This study aims to create a web-based dashboard that can facilitate the collection of information and data for the 9 criteria for the accreditation process of study programs. The method used in this research is the prototype method, which consists of stages (1) listening to customers, (2) building and improving prototypes, and (3) testing prototypes. The result to be obtained as an output in this research is an information system in the form of a dashboard that can facilitate monitoring of accreditation data for 9 (nine) criteria.